Legal Analysis of Crimes Against Children as Perpetrators of Bullying which Have Fatal Consequences on Victims - Putri, Darma; Daeng, Yusuf; S. F, Baginda; Rahmat, Khevin (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
The criminal act of bullying or harassment is identically known as an act of violence against children that occurs at school. In the event that bullying occurs at school, bullying is aggressive behavior carried out repeatedly by a person/group of students who have power, against other students/girls who are weaker, with the aim of hurting that person. Bullying is a negative social behavior where this behavior aims to hurt other people continuously. According to social norms, hurting other people is a violation, because everyone has the right to feel safe from other people's negative behavior. Bullying behavior in the school environment still continues to occur and is increasingly disturbing and the impact it will have on the victim will have a very negative impact on the victim. The phenomenon of bullying behavior in schools is increasingly emerging. This is reinforced by data from the Indonesian Child Protection Commission (KPAI) and the Federation of Indonesian Teachers' Unions (FSGI), bullying cases are still a terror for children in the school environment. From this data, it is known that cases of bullying in schools will increase during 2023. January-August 2023, there were 2,355 cases of violations of child protection. Of the reports received, 837 cases occurred within educational units, with 226 cases of bullying recorded in 2022. Then in 2021 there were 53 cases, and in 2020 there were 119 cases. Meanwhile, the types of bullying that victims often experience are physical bullying (55.5%), verbal bullying (29.3%), and psychological bullying (15.2%). For educational level, elementary school students were the most victims of bullying (26%), followed by middle school students (25%), and high school students (18.75%). The formulation of the problem in this study is how The Analysis of legal aspects related to criminal acts against children as perpetrators of bullying, and What are the negative impacts of criminal acts of bullying on the psychology of perpetrators and victims. The research method used by the author is normative juridical method carried out through a literature study that examines secondary data in the form of laws and regulations relating to criminal acts related to child abuse, and laws related to the analysis of criminal acts involving child perpetrators as well as research results and other references. The results of this study are in the Bullying is an act of violence against children, so based on the provisions in the Child Protection Law and its amendments, bullying is included as a criminal act. Basically, physical and verbal oppression is regulated in Article 76C of Law 35/2014 which reads as follows: Every person is prohibited from placing, allowing, carrying out, ordering to carry out, or participating in committing violence against children. Furthermore, if the above prohibition is violated, the perpetrator can be charged under Article 80 of Law 35/2014, namely: Every person who violates the provisions of Article 76C of Law 35/2014, will be sentenced to imprisonment for a maximum of 3 years and 6 months and/or a fine of a maximum of IDR 72 million. If a child suffers serious injuries, the perpetrator will be sentenced to imprisonment for a maximum of 5 years and/or a fine of a maximum of IDR 100 million. If a child dies, the perpetrator will be sentenced to imprisonment for a maximum of 15 years and/or a fine of a maximum of IDR 3 billion. Then oppression, harassment or bullying becomes bad behavior that can have a negative impact. The bad news is, anyone can become a victim of bullying. There are various forms of bullying behavior, ranging from verbal, non-verbal, to physical actions. Of course, all of this can have an impact on the victim's life. Even without realizing it, bullying behavior can also influence the perpetrator's behavior. The impact of bullying on victims is very diverse. The following include: Susceptible to Feeling Emotions, Difficulty Forming Relationships, Triggers Mental Disorders. Then. The following are some of the impacts of bullying for the perpetrator: Habitually carrying out impulsive activities, increasingly dull empathy, increased aggressive behavior, increasingly severe antisocial behavior, getting a negative label.